(untitled) - Takahashi, Baku (Bangkok, 2012)
The designations employed an the presentation of material in this information product do not imply the expression of any opinion whatsoever on the part of the food and agriculture organization of the United Nations (FAO) conerning the legal or development status of any country, terrritory, city or area or of its authorities.
Keywords: Fishery co-management,Quản lý thủy sản